2005
DOI: 10.1200/jco.2005.07.062
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and Neoplastic Risk in a Large Cohort of Patients With Polycythemia Vera

Abstract: The European Collaboration on Low-Dose Aspirin in Polycythemia Vera study documents that large international collaborative studies are feasible in this field, in which few epidemiologic data are available. The persistently high mortality rate from hematologic malignancies characterizes the unmet therapeutic need of polycythemic patients and suggests a priority for future studies in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
591
6
31

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 643 publications
(661 citation statements)
references
References 19 publications
33
591
6
31
Order By: Relevance
“…Low-dose ASA might have also contributed to the relatively low incidence of major thrombosis (18%), in the lower range of literature data [6,27], without increasing hemorrhagic complications compared to published observations [33]. Nevertheless, the high thrombotic risk according to Finazzi et al [28,29] confirmed its negative prognostic impact in terms of overall and thrombosis-free survival in both univariate and multivariate analysis.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Low-dose ASA might have also contributed to the relatively low incidence of major thrombosis (18%), in the lower range of literature data [6,27], without increasing hemorrhagic complications compared to published observations [33]. Nevertheless, the high thrombotic risk according to Finazzi et al [28,29] confirmed its negative prognostic impact in terms of overall and thrombosis-free survival in both univariate and multivariate analysis.…”
Section: Discussionmentioning
confidence: 83%
“…These parameters were used to define the thrombotic risk according to the recent definition by Finazzi and Barbui based on ECLAP data [28,29] (32,33) c Percent of chemotherapy-treated patients; some patients received more than one treatment for platelet counts were 400×10 9 /l, corresponding to the normal upper range, and 600×10 9 /l, the thrombocytosis threshold previously used by WHO guidelines for the diagnosis of essential thrombocythemia [31]. A leukocyte cutoff value of 15×10 9 /l was chosen, since it has been previously reported to be prognostically relevant in terms of thrombosis-free survival [32].…”
Section: Methodsmentioning
confidence: 99%
“…43 The largest prospective evaluation of risk factors for survival, incidence of thrombosis and hematological transformation is the ECLAP observational cohort study. 44 Patients younger than 65 years in the ECLAP Study had the lowest rate of thrombosis (2.5% patients per year), while with age older than 65 years and a positive history of thrombosis, the corresponding rate ranged from 6 to 10% patients per year. Of note were a consistent association between age 465 years and risk of leukemia and between duration of disease with risk of overt myelofibrosis.…”
Section: What To Do In Young Patients With Thrombosismentioning
confidence: 89%
“…According to knowledge from analyses done in the past era of the PVSG classification [7], older age ( 60 years) and a history of thrombosis are considered as standard risk factors for thrombosis and guide current treatment decisions [11]. Leukocytosis at diagnosis and the JAK2V617F mutation are suspected as novel disease-associated risk factors for vascular complications [12][13][14].…”
Section: Discussionmentioning
confidence: 99%